2016
DOI: 10.2174/1874210601610010680
|View full text |Cite
|
Sign up to set email alerts
|

A One-year Follow-up Study of a Tapered Hydrophilic Implant Design Using Various Placement Protocols in the Maxilla

Abstract: Purpose:To study the clinical/radiographic outcomes and stability of a tapered implant design with a hydrophilic surface when placed in the maxilla using various protocols and followed for one year.Methods:Ninety-seven consecutive patients treated as part of daily routine in two clinics with 163 tapered implants in healed sites, in extraction sockets and together with bone augmentation procedures in the maxilla were evaluated after one year in function. Individual healing periods varying from 0 to 6 months had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…All implants and prostheses remained in function following 1 year, giving a survival rate of 100%. This is in agreement with other 1-year follow-up studies using the Neoss implant system [ 9 , 23 ]. Radiographic analysis of the peri-implant bone showed that most of the bone remodeling occurred during the first 6 months in function (−0.49 ± 0.38 mm), and stable bone remodeling occurred between the 6-month and 1-year visit (+0.01 ± 0.28 mm).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…All implants and prostheses remained in function following 1 year, giving a survival rate of 100%. This is in agreement with other 1-year follow-up studies using the Neoss implant system [ 9 , 23 ]. Radiographic analysis of the peri-implant bone showed that most of the bone remodeling occurred during the first 6 months in function (−0.49 ± 0.38 mm), and stable bone remodeling occurred between the 6-month and 1-year visit (+0.01 ± 0.28 mm).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, no significant International Journal of Dentistry differences were found for bone remodeling between implants placed in the healed bone and those placed in fresh extraction sockets. Previous findings with the Neoss implant system also reported on minimal bone remodeling for the first year in function [9,23] as well as for longer follow-up periods [24,25]. In the current study, only implants with an ISQ value higher than 60 at insertion were included for immediate load.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Only 11 studies were eligible for full-text evaluation, of which, six studies were excluded. [27][28][29][30][31][32] The remaining five trials [33][34][35][36][37] were included for the present review ( Table 2). The hand search did not provide any further studies.…”
Section: Characteristics Of the Trial Settings And Investigatorsmentioning
confidence: 99%
“…The IST and ISQ values in this study were high. Zwaan et al [ 16 ] placed 163 implants in the maxilla and compared the IT at 50 Ncm, 40–45 Ncm, 30–35 Ncm, and ≤ 30 Ncm and found that the ISQ values were 76.2 ± 5.3, 72.3 ± 5.3, 70.0 ± 6.7, and 68.1 ± 6.2, respectively. The ISQ values were also reported to be higher for tapered implants than for straight implants.…”
Section: Discussionmentioning
confidence: 99%